Study of insect diversity in areas surrounding The Central Marsh in southern Iraq. Issue 1 (1st March 2022) - Kareem, Ali; Aljaafari, Raad K.; Abaas, Manar A.; Al-Zurfi, Sienaa M.; Fazaa, Nadheer A.; Al-Sheikhly, Omar F.; Haba, Mukhtar K.; Whittingham, Mark J.
Abstract: During the several visits in 2018 and 2019 to some areas surrounding Central Marsh in southern Iraq (CMSI) for conservation purposes. The fauna of insects from different sites and sessions of the CMSI are surveyed in this study; there were (18) species, (17) genera that belong to (16) families and (7) orders which are recorded in this investigation using sweeping nets and light traps. According to available references, 7 species are new records in the area of study. This is survey is important for updating insects diversity in central Marshlands in Iraq. A counting study is needed to understand more about insect distributions and their impacts on biodiversity in such an important area.